Data-driven comparison of urban sustainability towards sustainable urban development under sustainable development goals (SDGs): a review based on bibliometric analysis - Wang, Di; Dong, Liang; Di, Siyan (Frontiers in Energy Research, 2023)
As urbanization has increased rapidly, the issue of sustainability has become more prominent, and urban sustainability should be the key to achieving the sustainable agenda raised by the UN. This study combines bibliometrics and text mining to analyze the research progress of urban sustainability. A total of 1,031 keywords from 240 documents screened by the PRISMA method are coded to draw heat maps in accordance with the sustainable triple bottom line principle and its cross-scope (Environment, Society, Economics, Environment & Society, Environment & Economics, Society & Economics, Environment, and Society & Economics) with its emphasis on 17 SDGs. The innovation of this study is manifested as the use of heat maps. The results indicate that the existing relevant research still focuses on environmental protection. Besides the general “sustainability” topics, “land use,” “decision-making,” “green city,” and “eco-city” have been more discussed than others. For the SDGs, the SDG 6, 7, 9, 11, 12, and 15 represent clean water, affordable and clean energy, industry, innovation and infrastructure, sustainable cities and communities, and responsible consumption and production and life on land, respectively. Only a small part of the research has begun to focus on the sustainable development of the community. More comprehensive and complete insights should be gained into sustainable development. This study suggests that the research on urban sustainability will be further deepened, and it should be significantly integrated with SGDs and place a focus on the coupling of urban sustainability and economic growth.